Answer:
A
Step-by-step explanation:
(fg)(x) = f(x) × g(x)
= (x - 8)(x² + x - 1)
Each term in the second factor is multiplied by each term in the first factor, that is
x(x² + x - 1) - 8(x² + x - 1) ← distribute both parenthesis
= x³ + x² - x - 8x² - 8x + 8 ← collect like terms
= x³ - 7x² - 9x + 8 → A
There are no restrictions on the domain.
Answer:
2x for the first term
The whole thing is 2x+3
Step-by-step explanation:
Think of it like normal division
What will get the closest answer to 2x^2+x?
2x*x-1=2x^2-2x
Now the expression is 3x-3 so if you but 3 than it becomes 3x-3 which would be a remainder of 0
X: liters of 15% orange juice
y: liters of 10% orange juice
x+y=5L
y=5L - x
x liters of 15% orange juice plus y liters of 10% orange juice makes 5 liters of 12% orange juice in equation form:
0.15x+0.10y = 0.12(5L)
0.15x+0.10(5L-x)=0.12(5L)
0.15x+0.5-0.10x=0.6
0.05x=0.1L
x=2L
so y = 3L
so you need 2 liters of 15% orange juice and 3 liters of 10% orange juice
-5x 2/7 =
−10x/7
srry if it is wrong man but that is what i got
Here you go!!! I hope this helps